Novel functions of the primary cilium in bone disease and cancer. Issue 3 (28th May 2019) - Shi, Wengui; Ma, Zhijian; Zhang, Gengyuan; Wang, Chen; Jiao, Zuoyi
Abstract: The primary cilium, a sensory organelle that emanates from the cell surface of most mammalian cell types during growth arrest, has attracted the attention of many researchers over the past decade. Recently, a large number of new findings have assigned novel functions and roles to the primary cilium in signal transduction and related diseases, which has greatly augmented the importance of the cilium in human health and development. Here, we review emerging evidence supporting the primary cilium as a sensory organelle in signal transduction in microgravity, electromagnetic field sensing, chemosensation and tumorigenesis. We also present an overview of signal transduction crosstalk associated with the primary cilium in bone disease and cancer, including primary cilium‐related Ca 2+ signaling, parathyroid hormone signaling, cAMP signaling, BMP/Smad1/5/8 signaling and Wnt signaling. We anticipate that emerging discoveries about the function of the primary cilium will provide novel insight into the molecular mechanisms of stimulus sensation, signal transduction and pathogenesis.